Substrate effect on bacterial communities from constructed wetlands planted with Typha latifolia treating industrial wastewater - Calheiros, Cristina S.C. (2010)
Constructed wetlands (CWs) have been recognized as being able to effectively treat wastewater from municipal and industrial sources. This study focused on the effect of different substrates and long-term operation of horizontal subsurface flowCWstreating tannery wastewater on the bacterial communities. The CWs were planted with Typha latifolia in three types of substrate: two units with different types of expanded clay aggregates and one unit with fine gravel. Another unit with expanded clay was left unvegetated. Changes in the bacterial community related to the type of substrate, different hydraulic loading rates and along CW operationwere examined using denaturating gradient gel electrophoresis (DGGE). Bacterial enumerationwas also performed and several bacterial isolateswere retrieved from the CWs. Phylogenetic affiliations of those isolates were obtained on the basis of 16S rRNA gene sequences and revealed that they were closely related to the genera Bacillus (TM1S1, TM1R3, TNR1 and TAR1), Paracoccus (TM1R2), Pseudomonas (TM1R1) and Halomonas (TM1S2). The type of substrate and the presence of T. latifolia had a major effect on the species richness and the structure of bacterial communities as inferred by numerical analysis of DGGE profiles.